Identifying Abundant Immunotherapy and Other Targets in Solid Tumors: Integrating RNA-seq and Mass Spectrometry Proteomics Data Sets. Issue 2 (March 2017) - Zhao, Wei; Fitzgibbon, Matthew; Bergan, Lindsay; Clegg, Nigel; Crispin, David; Mills, Gordon B.; McIntosh, Martin
Abstract : Abstract: RNA-seq and mass-spectrometry proteomics combined with growing data repositories have greatly increased the capacity to identify candidate proteins or protein sequence variants that share properties of ideal therapy targets, which include being abundant in cancer cells, absent or rare in adult organs (especially vital organs), and shared by many patient tumors. RNA-seq and fixed content arrays can identify genes that are overexpressed or misexpressed in cancer. RNA-seq is uniquely suited to identifying cancer-specific sequence variants. We review factors relevant for determining whether products of genes that are abundant or differentially abundant in RNA-seq are concordant or discordant with proteins that are identified as abundant or differentially abundant in mass-spectrometry proteomics assays.